The Green Path: FDI's Influence on Asia's Sustainable Economic Growth - Anh Le Ngoc; Almas Heshmati (Institute of Labor Economics (IZA), 2025)
This study examines the dual impact of Foreign Direct Investment (FDI) on sustainable economic growth in Asia, focusing on its effects on Green GDP, greenhouse gas (GHG) emissions, and the Environmental Performance Index (EPI). Using data from 38 Asian countries spanning 1999 to 2022 and employing a two-step GMM regression analysis, the findings reveal that while FDI positively influences Green GDP growth, it concurrently exacerbates GHG emissions and reduces EPI scores. These results underscore the paradoxical role of FDI in fostering economic growth while posing environmental challenges. The study highlights the importance of robust environmental policies, investment in green technologies, and regional cooperation to align FDI with sustainability goals. It also emphasizes the need for a balanced approach to leverage FDI's economic benefits without compromising environmental integrity. This research contributes to the literature by providing a comprehensive analysis of FDI's environmental and economic implications in the Asian context, offering policy recommendations for achieving sustainable development.
Keywords: F20; F21; O11; O44; O53; Q56; 330; sustainable economic growth; green economy; foreign direct investment; Asia